Analyzing the effects of Khorramabad - Zal bridge highway construction on rural development Eastern Miankoh villages - Mehrshad tolabinejad; Hossein farahani (تحقیقات کاربردی علوم جغرافیایی)
Transportation networks‚ particularly roads as a linking elements between settlements has a significant role in the exchange of flows between urban and rural areas and also rural development .The aim of this paper is to study the effect of highways construction and expanding transportation on rural stable development in the rural district of eastern Miankouh which by using survey method (questionnaire) have been turned to the studying of highways construction on development quality of adjacent villages in this rural district. In this study ‚mean time of defining the population community (514 family)‚ the 103 family was selected as a sample with Cochran formula (12 villages).The result of achieved data analysis‚ on the basis of‚ fitting regression test‚ linear regression and path analysis showed that the most general effect of highway construction is relevant to the environmental dimension with amount of (0/591) so that the contamination of soil and water resources have been increased in rural areas. Also using of fertilizers and pesticides is been prevalent. The amount of demolition of water resources such as springs and water channeling have been increased in the rural boundary. and also pastures‚ forests and fertile lands have been allocated to the building constructions and forming dimension with amount of (0/058) has the least overall effect on the rural stable development in the boundary of studying area.